EFEKTIVITAS PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X SMA NEGERI 8 PEKANBARU - Nofita Damayanti; Nahor Murani Hutapea; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is the low ability of mathematical problem solving skill of students class X SMA Negeri 8 Pekanbaru. The purposes of this research are 1) to describe the difference of mathematical problem solving skill of students who study through PBL model with student who study through conventional learning with scientific approaching; 2) to examine the improvment of mathematical problem solving skill of students who study through problem solving skill and students who study through conventional learning with scientific approaching. This research is an experimental research (quasi experiment) with The Nonequivalent Pretest-Posttest Control Group Design. The population of this research is all students of class X SMA Negeri 8 Pekanbaru. The sample of this research consits of two classes, class X MIPA1 as experiment class and X MIPA3 as control class. The research instruments are mathematical prior knowledge test and matehmatical problem solving ability test. Mathematical prior knowledge test score were used to select the sample of this research. Data were analysed by using Independent sample T-Test preceded by normality test and homogenity of variances test. The result showed that the improvement of mathematical problem solving ability of students who study through PBL model is higher than student who study through conventional learning with scientific approaching.Key Words: Problem Based Learning, Mathematical Problem Solving Ability